Synthesis, Functionalization, and Bioapplications of Two-Dimensional Boron Nitride Nanomaterials - Emanet, Melis; Sen, Özlem; Taşkin, Irem Çulha; Çulha, Mustafa (Frontiers in Bioengineering and Biotechnology, 2019)
Two-dimensional boron nitride nanostructures (2D-BNNs) have been increasingly investigated for their applications in several scientific and technological areas. This considerable interest is due to their unique physicochemical properties including high hydrophobicity, heat and electrical insulation, resistance to oxidation, antioxidation capacity, thermal conductivity, high chemical stability, mechanical strength, and hydrogen storage capacity. They are also used as fillers, antibacterial agents, protective coating agents, lubricants, boron neutron capture therapy agents, nanocarriers for drug delivery, and receptor phase in chemosensor. The investigations for their use in medicine and biomedicine are very promising including cancer therapy and wound healing. In this review, 2D-BNNs synthesis and their surface modification strategies, biocompatibility and bio-application studies are discussed. Finally, a perspective for the future use of these novel nanomaterials in the biomedical field is provided.